2022
DOI: 10.1038/s41598-022-13542-1
|View full text |Cite
|
Sign up to set email alerts
|

E-learning is a burden for the deaf and hard of hearing

Abstract: When considering deaf and hard of hearing (DHH) population, research recognizes that fatigue due to communication challenges and multi-focal attention allocation is a significant concern. Given the putative heightened demands of distance learning on deaf and hard of hearing students, we investigate how an online environment might differently affect deaf and hard of hearing participants, compared to hearing participants, Portuguese Sign Language (PSL) users and non-users. Our findings show that the deaf and har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…In accordance with the development of the current era, integrating digital learning tools into the teaching and learning process is one of the most preferred or recommended methods in the process of educating deaf learners (Ahmed & Hasegawa, 2022). However, another study states that in using e-learning during distance learning at the time of Covid-19 pandemic, deaf and hearing impaired learners faced higher levels of fatigue and showed lower performance due to several dimensions of academic challenges leading to further inequality and obstacles that affect their participation opportunities (Rodrigues et al, 2022).…”
Section: Characteristics Of Deaf Students In Learningmentioning
confidence: 99%
“…In accordance with the development of the current era, integrating digital learning tools into the teaching and learning process is one of the most preferred or recommended methods in the process of educating deaf learners (Ahmed & Hasegawa, 2022). However, another study states that in using e-learning during distance learning at the time of Covid-19 pandemic, deaf and hearing impaired learners faced higher levels of fatigue and showed lower performance due to several dimensions of academic challenges leading to further inequality and obstacles that affect their participation opportunities (Rodrigues et al, 2022).…”
Section: Characteristics Of Deaf Students In Learningmentioning
confidence: 99%
“…Additionally, research showed a link between low scores achieved by the deaf and hard-of-hearing group and post-task fatigue rates, with a difference that was noticeably wider when compared to the hearing group. Along with this the deaf and hard of hearing population may be at a disadvantage in several ways due to increased fatigue rates, creating even more inequities and limitations that influence well-being and engagement chances (Rodrigues, 2022).…”
Section: One Of the Participants Explainedmentioning
confidence: 99%
“…Concerning higher-level effects of visual fatigue, recent studies (Csathó et al, 2012 ; Cao et al, 2014 ; Rodrigues et al, 2022 ) utilized a visual attention task to characterize the decline in cognitive performance showing significant adverse effects of fatigue on task performance, particularly when the perceptual load of the target stimuli was high. This phenomenon also relates to the so-called cognitive fatigue—a mental exhaustion that can affect task performance and subjective affective evaluation (Bess and Hornsby, 2014 ; Karshikoff et al, 2017 ; Ioannucci et al, 2020 ; Guillemin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%